The Role of Spiritual Intelligence in Enhancing Female Employee Performance and Reducing Turnover Intention in the Economic Landscape - Noor, Murniati; Purwati, Astri Ayu; Irman, Mimelientesa; Rizki, Muhammad; Salleh, Mohd Fairuz Md. (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the effect of incentives, job stress, and role conflict on performance and turnover intention among female nurses at RSUD dr RM Pratomo Bagansiapiapi, Rokan Hilir Regency. The population studied consisted of all female nurses working at the hospital, with a total of 117 people. Using the total sampling method, all members of the population were sampled in this study. Data analysis was carried out using the Structural Equation Modeling (SEM) approach through Partial Least Squares (PLS). The results showed that incentives have a significant positive effect on nurse performance, while role conflict has a significant negative effect on performance. In addition, job stress has a significant positive effect on turnover intention. The study also found that spiritual intelligence plays a moderating role in the effect of incentives on turnover intention, but has no moderating effect in the relationship between job stress and turnover intention. The findings are expected to provide insights for hospital management in managing nurses' performance and reducing turnover intention.